Fetal ventricular strain in uncomplicated and selective growth‐restricted monochorionic diamniotic twin pregnancies and cardiovascular response in pre‐twin–twin transfusion syndrome. (2nd November 2020) - Wohlmuth, C.; Agarwal, A.; Stevens, B.; Johnson, A.; Moise, K. J.; Papanna, R.; Donepudi, R.; Bell, C. S.; Averiss, I. E.; Gardiner, H. M.
ABSTRACT: Objectives: Our primary aim was to confirm whether intertwin discordance in ventricular strain and ductus venosus (DV) time intervals predicts twin–twin transfusion syndrome (TTTS). Secondary aims were to create gestational‐age ranges for ventricular strain in uncomplicated monochorionic diamniotic (MCDA) twin pregnancies without selective intrauterine growth restriction (sIUGR) and to characterize the relationship of ventricular strain with gestational age in MCDA twin pregnancies with sIUGR that did not develop TTTS. Methods: In the period 2015–2018, we enrolled 150 MCDA twin pregnancies consecutively into this prospective, blinded study of global longitudinal left and right ventricular strain. With the observer blinded to twin pairing and pregnancy outcome, videoclips of the four‐chamber view, which had been recorded during ultrasound surveillance in the usual window for development of TTTS (16–26 completed gestational weeks), underwent offline measurement of strain. Uncomplicated MCDA twin pregnancies, without sIUGR, were used to test the association between strain, gestational age and estimated fetal weight using mixed‐effects multilevel regression. Inter‐rater reliability was tested in 208 strain measurements in 31 fetuses from pregnancies which did not develop TTTS and within‐fetus variation was assessed in 16 such fetuses, in which multiple four‐chamber views were taken on the same day. The effect of sIUGR on strain in otherwise uncomplicated MCDA twin pregnancy was analyzed. MCDA twin pregnancies were defined as 'pre‐TTTS' when, having been referred for TTTS evaluation, they did not satisfy Quintero staging criteria, but subsequently developed TTTS requiring laser treatment. MCDA pregnancies which did not develop TTTS comprised the 'non‐TTTS' group. Cardiovascular parameters measured in these cases included tissue Doppler parameters and DV early filling time as a percentage of the cardiac cycle (DVeT%). Intertwin strain and DVeT% discordance was compared between non‐TTTS and pre‐TTTS cases, matched for gestational age. Results: Paired strain data were available for intertwin comparison in 127/150 MCDA twin pregnancies, comprising 14 pre‐TTTS and 113 non‐TTTS pregnancies, after exclusions. Scans were collected at a median frame rate of 97 (range, 28–220) Hz. Laser therapy was performed at a median gestational age of 20.6 (range, 17.2–26.6) weeks. There were no group differences in right (RV) or left (LV) ventricular strain discordance between 68/113 non‐TTTS and 13/14 pre‐TTTS MCDA twin pregnancies < 20 completed gestational weeks (RV, P  = 0.338; LV, P  = 0.932). DVeT% discordance > 3.6% was found in eight of 13 pre‐TTTS pregnancies. In non‐TTTS pregnancies, the estimated variability in ventricular strain within each twin during the day was high (RV, 19.7; LV, 12.9). However, within each pair (intertwin variation), variability was low (RV, 5.5; LV, 2.9). Interclass correlation reflecting the proportion of total variability represented by the variability between twin pairs was low (RV, 0.22; LV, 0.18). Both RV ( P  < 0.001) and LV ( P  = 0.025) strain showed a negative association with gestational age. Among non‐TTTS MCDA twin pregnancies, LV strain was, on average, higher by 1.83 in sIUGR compared with normally grown fetuses ( P  = 0.023), with no statistically significant difference in RV strain ( P  = 0.271). Conclusions: Although ventricular strain has been reported previously as a possible predictor of developing TTTS, in this blinded, prospective study, we found no significant intergroup differences in ventricular strain in pre‐TTTS compared with age‐matched non‐TTTS MCDA twin pregnancies. We recommend using DVeT% discordance as a more practical screening tool in MCDA twin pregnancies. This study also provides new information on the changes with gestational age, and the biological and technical variation, of global longitudinal ventricular strain in uncomplicated MCDA twin pregnancies and those with isolated sIUGR. © 2019 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.